2019
DOI: 10.21037/gs.2019.08.03
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau “Black Forest” mutation inherited in a large Chinese family

Abstract: Background: The Von Hippel-Lindau (VHL) p.Tyr98His (Y98H) mutation is designated as the "Black Forest" founder mutation and has been previously reported in Western countries. This study reports the first recorded Chinese VHL family with the "Black Forest" mutation in Asia.Methods: Paired whole-exome sequencing (WES), Sanger sequencing and immunohistochemistry (IHC) were performed on samples from a large Chinese family to confirm the causative mutation and mutation carriers in the family. Clinical manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
5
0
3
Order By: Relevance
“…A total of 52 studies, assessing 840 participants with vHL type 2, provided information on the frequency of PPGL. Most of these studies were conducted in Europe ( n =18) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 62 , 66 , 68 , 70 , 71 , 72 , 73 , 76 , 83 , 91 , 92 ), followed by Eastern Asia ( n =17) ( 35 , 36 , 40 , 44 , 45 , 47 , 48 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 86 , 87 ) and North America ( n =9) ( 53 , 59 , 60 , 61 , 63 , 64 , 65 , 69 , 84 ). All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 52 studies, assessing 840 participants with vHL type 2, provided information on the frequency of PPGL. Most of these studies were conducted in Europe ( n =18) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 62 , 66 , 68 , 70 , 71 , 72 , 73 , 76 , 83 , 91 , 92 ), followed by Eastern Asia ( n =17) ( 35 , 36 , 40 , 44 , 45 , 47 , 48 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 86 , 87 ) and North America ( n =9) ( 53 , 59 , 60 , 61 , 63 , 64 , 65 , 69 , 84 ). All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , …”
Section: Resultsmentioning
confidence: 99%
“…All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , 87 , 88 )). Six studies reported a consecutive sample ( 16 , 17 , 29 , 66 , 77 , 78 ), whereas in 39 studies a convenience sample was assessed ( 21 , 25 , 35 , 45 , 47 , 53 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations